Polyolefin resin composition

By using specific ethylene-α-allylpropylene copolymers and specific polymerization conditions, the problem of the drop in impact strength of traditional polypropylene materials at low temperatures is solved, and a balance of high transparency, good impact strength and low temperature performance is achieved.

JP7673388B2Active Publication Date: 2025-05-09JAPAN POLYETHYLENE CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020198465
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-13
Filing Date
2020-11-30
Publication Date
2025-05-09
Estimated Expiration
2040-11-30

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a balance between high transparency, good impact strength and low temperature performance in food packaging materials at the same time. Especially in frozen food packaging, traditional polypropylene materials have significantly reduced impact strength at low temperatures.

Method used

A specific ethylene-α-allylpropylene copolymer is used, which has a specific long-chain branch index and a narrow inverse co-omonomono composition distribution index, and is developed through specific polymerization conditions and catalysts to improve the cold impact strength, rigidity and transparency of the polypropylene resin.

Benefits of technology

It significantly improves the cold impact strength and transparency of polypropylene resin, while maintaining good rigidity and plastic forming performance, and is suitable for high-demand applications such as frozen food packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007673388000005
    Figure 0007673388000005
  • Figure 0007673388000006
    Figure 0007673388000006
  • Figure 0007673388000007
    Figure 0007673388000007
Patent Text Reader

Abstract

To provide a resin composition for improving rigidity, transparency, cold resistance and thermal moldability of polypropylene at high level.SOLUTION: A polyolefin-based resin composition contains at least 50-90 wt.% of a polypropylene-based resin of the following component (A), and 10-50 wt.% of a polyethylene-based resin of the following component (B). (A) Polypropylene that may contain α-olefin having 2 to 20 carbon atoms other than propylene as a comonomer, having a specific MFR. (B) Copolymer with α-olefin that mainly contains ethylene and has 3 to 18 carbon atoms, having specific density, MFR, molecular weight distribution Mw / Mn, molecular weight distribution Mz / Mw and ramification index g'.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyolefin resin composition containing polypropylene as a main component, a sheet and a molded article which are used in various industrial fields. [Background technology]

[0002] In recent years, plastic films, sheets, injection molded products, pipes, extrusion molded products, blow molded products, etc. have come to be widely used in various industrial fields. In particular, polyolefin resins (olefin polymers) are widely used because they are inexpensive, lightweight, and have excellent moldability, rigidity, impact strength, transparency, chemical resistance, and recyclability. In particular, polypropylene is increasingly being used in food packaging sheets because of its rigidity and transparency, but polypropylene has not been fully adopted for chilled or frozen food packaging because its impact resistance drops sharply at low temperatures below 0°C.In addition, in terms of formability, its low elongational viscosity means that holes and uneven thickness are likely to occur when forming wide, deep-drawn shapes using vacuum forming or other methods.

[0003] For example, polypropylene with excellent transparency includes propylene homopolymer (homo PP) and crystalline random copolymer with ethylene (random PP), but these have the drawback of poor impact resistance, and blending with general polyethylene or olefin-based rubber is known as a method to improve these. However, blending with general polyethylene or olefin-based rubber has the drawback of significantly reducing transparency and rigidity. On the other hand, polypropylene with improved impact resistance includes so-called impact copolymers (ICPs) in which polyethylene components and amorphous or low-crystalline propylene-ethylene copolymers are dispersed in crystalline polypropylene by copolymerization with ethylene, but ICPs have the drawback of being extremely poor in transparency. Therefore, it was difficult to achieve high levels of transparency, rigidity, and impact resistance in polypropylene-based resins using conventional technology.

[0004] In sheet molding, the moldability of polyolefin resins is dependent on the properties of the molten state, and generally, if the fluidity or elongational viscosity is insufficient, it may be difficult to ensure sufficient moldability. Conventionally, blending with high-pressure low-density polyethylene (HPLD), which has excellent moldability, has been known as a method for improving the moldability of polypropylene resins, but when HPLD is used, although moldability is obtained, there are problems such as insufficient improvement in impact strength and deterioration of transparency. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 09-031265 [Patent Document 2] JP 2000-072938 A [Patent Document 3] JP 2006-312753 A [Patent Document 4] Japanese Patent Application Publication No. 60-090203 [Patent Document 5] Japanese Patent Application Publication No. 10-298234 Summary of the Invention [Problem to be solved by the invention]

[0006] In view of the above-mentioned problems of the conventional art, an object of the present invention is to provide an ethylene-α-olefin copolymer which is excellent in improving the molding processability of a polypropylene resin composition and, at the same time, is suitably excellent in improving the balance between impact strength and rigidity, and a polyolefin resin composition containing the same. [Means for solving the problem]

[0007] As a result of intensive research into solving the above problems, the present inventors have found that an ethylene-α-olefin copolymer having a specific long-chain branching index, a relatively narrow reverse comonomer composition distribution index, and specific MFR and density is excellent in terms of improving the balance between cold impact strength, rigidity, transparency, and moldability of a polypropylene resin composition, particularly as a polyethylene for resin modification, and have completed the present invention based on these findings. Furthermore, the present inventors have also found that the above ethylene-α-olefin copolymer having a desired long-chain branching index and composition distribution index can be efficiently obtained by carrying out polymerization under controlled specific polymerization conditions using a specific catalyst newly developed by the present applicant in recent years.

[0008] That is, according to a first aspect of the present invention, there is provided a polyolefin resin composition having the following characteristics: A polyolefin resin composition comprising at least 50 to 90% by weight of a polypropylene resin, component (A), and 10 to 50% by weight of a polyethylene resin, component (B), (wherein the total amount of components (A) and (B) is taken as 100% by weight). (A) Polypropylene which may contain an α-olefin having 2 to 20 carbon atoms other than propylene as a comonomer, and has an MFR (JIS-K6758) of 0.1 to 50 g / 10 min. (B) A copolymer containing ethylene as a main component and an α-olefin having 3 to 18 carbon atoms, which satisfies the following conditions (B-1) to (B-5): (B-1) MFR (JIS-K7210) is 0.1 to 10g / 10min. (B-2) Density: 0.880 to 0.940 g / cm 3 . (B-3) The molecular weight distribution Mw / Mn measured by gel permeation chromatography (GPC) is 3.0 to 5.5. (B-4) The molecular weight distribution Mz / Mw measured by GPC is 2.0 to 6.0. (B-5) The minimum value (gc) of the branching index g' measured by a GPC measuring device combining a differential refractometer, a viscosity detector and a light scattering detector in the molecular weight range of 100,000 to 1,000,000 is 0.40 to 0.85.

[0009] In addition, according to the second aspect of the present invention, there is provided a polyolefin resin composition according to the first aspect of the present invention, wherein the polyolefin resin composition further contains 0.03 to 2 weight % of a nucleating agent of component (C) (wherein the total amount of components (A), (B) and (C) is taken as 100 weight %).

[0010] According to a third aspect of the present invention, there is provided a single-layer or multi-layer sheet characterized by having one or more layers made of the resin composition described in the first or second aspect of the present invention.

[0011] According to a fourth aspect of the present invention, there is provided a molded article obtained from the sheet according to the third aspect of the present invention.

[0012] According to a fifth aspect of the present invention, there is provided a modifier (B) for polypropylene-based resins, comprising the following component (B) a polyethylene-based resin: (B) A copolymer containing ethylene as a main component and an α-olefin having 3 to 18 carbon atoms, which satisfies the following conditions (B-1) to (B-5): (B-1) MFR (JIS-K7210) is 0.1 to 10g / 10min. (B-2) Density: 0.880 to 0.940 g / cm 3 . (B-3) The molecular weight distribution Mw / Mn measured by gel permeation chromatography (GPC) is 3.0 to 5.5. (B-4) The molecular weight distribution Mz / Mw measured by GPC is 2.0 to 6.0. (B-5) The minimum value (gc) of the branching index g' measured by a GPC measuring device combining a differential refractometer, a viscosity detector and a light scattering detector in the molecular weight range of 100,000 to 1,000,000 is 0.40 to 0.85. Effect of the Invention

[0013] The polyolefin resin composition of the present invention satisfies the melt tension required for molding processability, significantly improves the cold impact strength of polypropylene, and has excellent rigidity and transparency, thereby exerting excellent effects. [Brief description of the drawings]

[0014] [Figure 1] 1 is a graph showing the baseline and interval of a chromatogram used in a gel permeation chromatography (GPC) method. [Diagram 2] FIG. 2 is a plot of extensional viscosity when an inflection point of extensional viscosity is observed. [Diagram 3] FIG. 1 is a plot of extensional viscosity where no inflection point is observed in extensional viscosity. [Figure 4] (a) shows the molecular weight distribution curve measured based on the molecular weight (M) obtained from MALLS and the concentration obtained from RI, and (b) shows the branching index (g') at molecular weight (M). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention relates to a polyolefin resin composition containing at least a polypropylene resin as component (A) and a polyethylene resin as component (B). The components used in the present invention will now be described in detail.

[0016] 1. Component (A) Polypropylene resin Component (A) is a polypropylene resin used in the polyolefin resin composition of the present invention, which is a polypropylene that may contain an α-olefin having 2 to 20 carbon atoms other than propylene as a comonomer, and more specifically, is a propylene homopolymer (A1) or a copolymer (A2) of propylene and an α-olefin having 2 or 4 to 20 carbon atoms, with propylene as the main component. In this specification, the term "main component" refers to the component that occupies the highest proportion of the substance. The polypropylene of the component (A) has an MFR (JIS-K6758: temperature 230° C., load 2.16 kgf) of 0.1 to 50 g / 10 min. Here, the MFR of component (A) refers to the value measured under conditions of 230° C. and a load of 21.18 N (2.16 kg) in accordance with JIS K6758 "Testing Method for Polypropylene." In addition, as long as the properties after mixing are within the above-mentioned ranges, the mixture may be a mixture of two or more polypropylenes corresponding to (A1) or (A2), and the mixing may be performed by any method. One or more α-olefins having 2 to 20 carbon atoms other than propylene, which are comonomers, may be used, and examples thereof include ethylene, 1-butene, 1-pentene, hexene, 1-heptene, 1-octene, 4-methyl-pentene-1, 4-methyl-hexene-1, and 4,4-dimethyl-pentene-1.

[0017] 2. Component (B) Polyethylene resin Component (B) is a polyethylene resin used in the polyolefin resin composition of the present invention, and is a copolymer of ethylene with an α-olefin having 3 to 18 carbon atoms (hereinafter, component (B) may be referred to as an ethylene polymer (B)). The ethylene polymer (B) is a copolymer of ethylene and one or more α-olefins, and is an ethylene polymer having a special long-chain branched structure. That is, the ethylene polymer (B) used in the present invention must satisfy all of the conditions (B-1) to (B-5) described below, and preferably further satisfy one or more of the conditions (B-6) to (B-11). In particular, the characteristics represented by the conditions (B-6) and (B-7), and preferably the characteristics represented by the conditions (B-5), (B-6), (B-7), and (B-9) are stipulations that mean a characteristic long chain branch structure that is interpreted as containing a considerable amount of relatively short long chain branch structures that are sufficiently developed to be able to be entangled with each other at a level at which elongation strain hardening behavior is observed. In addition, the condition (B-3) indicates that the ethylene polymer (B) used in the present invention is an ethylene copolymer having a long chain branch structure of a type having a relatively narrow molecular weight distribution.

[0018] 2-1.Conditions (B-1) Melt flow rate (MFR) of ethylene polymer (B) B The MFR is preferably in the range of 0.1 to 10 g / 10 min, more preferably 0.1 to 1.5 g / 10 min. B When the MFR is 0.1 g / 10 min or more, the moldability is excellent. B When the compressive strength is 10 g / 10 min or less, deterioration in impact resistance, mechanical strength, etc. can be prevented. Here, the MFR of the ethylene polymer (B) B Refers to the value measured under conditions of 190°C and a load of 21.18N (2.16kg) in accordance with JIS K7210 "Test method for melt mass-flow rate (MFR) and melt volume rate (MVR) of plastics - thermoplastics."

[0019] 2-2.Conditions (B-2) In addition, the density of the ethylene polymer (B) B is 0.880~0.940g / cm 3 0.915~0.940g / cm 3 is preferable, and 0.916 to 0.940 g / cm 3 More preferably, the density B When the density is within this range, the balance between impact resistance and rigidity is excellent. B If the density is too low, the stiffness tends to decrease. B If it is too high, the impact resistance and transparency may be impaired. Here, the density of the ethylene polymer (B) B refers to the value measured by the following method.

[0020] The pellets are hot pressed to prepare a 2 mm thick pressed sheet, which is then placed in a 1000 ml beaker, filled with distilled water, covered with a watch glass, and heated with a mantle heater. After the distilled water boils, the beaker is placed on a wooden stand and left to cool for 60 minutes. The amount of boiled distilled water after 60 minutes of boiling is 500 ml, and the time required for the temperature to reach room temperature is adjusted to not less than 60 minutes. The test sheet is immersed in the water at approximately the center so as not to come into contact with the beaker or the water surface. The sheet is annealed at 23°C and 50% humidity for 16 to 24 hours, and then punched out to 2 mm in length and width, and measured at a test temperature of 23°C in accordance with JIS K7112 "Method for measuring density and specific gravity of plastics - non-foamed plastics".

[0021] 2-3.Conditions (B-3) Furthermore, the molecular weight distribution [Mw / Mn] of the ethylene polymer (B) measured by gel permeation chromatography (GPC) B That is, the ratio of weight average molecular weight (Mw) to number average molecular weight (Mn) (hereinafter also referred to as Q value) is 3.0 to 5.5. When the Q value is 3.0 or more, it is easy to mix with component (A). When the Q value is 5.5 or less, the effect of improving impact resistance is sufficiently obtained, and the balance between impact resistance and rigidity is excellent. From the viewpoint of the balance between impact resistance and rigidity, the upper limit of the Q value is preferably 5.0 or less, more preferably 4.5 or less. The lower limit of the Q value is preferably 3.5 or more, more preferably 4.0 or more.

[0022] 2-4.Conditions (B-4) Furthermore, the molecular weight distribution [Mz / Mw] of the ethylene polymer (B) measured by gel permeation chromatography (GPC) B That is, the ratio of Z-average molecular weight (Mz) to weight-average molecular weight (Mw) is 2.0 to 6.0. Molecular weight distribution [Mz / Mw] B When it is within the above specified range, the balance between formability and strength is excellent.

[0023] Gel Permeation Chromatography (GPC) Method In the present invention, the weight average molecular weight (Mw), number average molecular weight (Mn) and Z average molecular weight (Mz) of the ethylene polymer (B) are those measured by gel permeation chromatography (GPC). The conversion from retention volume to molecular weight is performed using a calibration curve prepared in advance using standard polystyrenes. The standard polystyrenes used are all the following brands manufactured by Tosoh Corporation: F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, and A1000. A calibration curve is created by injecting 0.2 mL of a solution dissolved in ODCB (containing 0.5 mg / mL BHT) so that each is 0.5 mg / mL. The calibration curve uses a cubic equation obtained by approximating with the least squares method. A general-purpose calibration curve is used for conversion to molecular weight, referring to "Size Exclusion Chromatography" by Mori Sadao (Kyoritsu Shuppan). The viscosity equation used in this case is [η] = K × M α The following values ​​are used: PS:K = 1.38 x 10 -4 , α=0.7 PE:K = 3.92 x 10 -4 , α=0.733

[0024] The GPC measurement conditions are as follows: Apparatus: Waters GPC (ALC / GPC 150C) Detector: FOXBORO MIRAN 1A IR detector (measurement wavelength: 3.42 μm) Column: Showa Denko AD806M / S (3 columns) Mobile phase solvent: o-dichlorobenzene Measurement temperature: 140℃ Flow rate: 1.0ml / min Injection amount: 0.2ml Sample preparation: Prepare a 1 mg / mL solution of the sample using ODCB (containing 0.5 mg / mL BHT) and dissolve the sample at 140° C. for approximately 1 hour. The baseline and intervals of the obtained chromatogram are as shown in FIG.

[0025] 2-5.Conditions (B-5) Furthermore, the ethylene polymer (B) has a branching index g' of 0.40 to 0.85, preferably 0.50 to 0.85, more preferably 0.50 to 0.80, still more preferably 0.50 to 0.77, and particularly preferably 0.51 to 0.75, in terms of the minimum value (gc) in the molecular weight range of 100,000 to 1,000,000, as measured by a GPC measuring device combining a differential refractometer, a viscosity detector, and a light scattering detector. C If the value is 0.85 or less, the effect of improving the molding processability when blended with a polyolefin resin can be sufficiently exhibited. C When the value is 0.40 or more, the molding processability of the polyolefin resin is improved, and it is possible to prevent a decrease in impact strength, particularly low-temperature impact resistance, and a deterioration in transparency. In the present invention, the gc value of the ethylene polymer (B) is a method for evaluating the amount of long chain branches using a molecular weight distribution curve and a branching index (g') calculated from the following GPC-VIS measurement.

[0026] 2-6.Conditions (B-6) Furthermore, the ethylene polymer (B) component has a maximum elongational viscosity after strain hardening of η(t) (unit: Pa·sec) measured at a temperature of 170°C and an elongational strain rate of 2 (unit: 1 / sec) in a double logarithmic plot of the elongational viscosity η(t) (unit: Pa·sec) versus the elongational time t (unit: sec). Max (t1), the approximate straight line of the elongation viscosity before curing is η Linear (t), then η Max (t1) / η Linear Strain hardening defined by (t1) [λmax(2.0)] B is, for example, 1.2 to 30.0, preferably 1.2 to 20.0, more preferably 1.2 to 10.0, still more preferably 1.2 to 5.0, and particularly preferably 1.2 to 3.0. Here, the approximation line of the extensional viscosity before curing refers to the tangent line with the smallest slope among the tangent lines of the curve of the log-log graph within the range t corresponding to the strain amount of 0.2 to 1.0 (however, the slope is 0 or a positive value). This [λmax(2.0)] B The value indicates the degree of development of long chain branches introduced into the ethylene polymer (B). [λmax(2.0)] BWhen [lambdamax(2.0)] is 1.2 or more, the ethylene polymer (B), the polyolefin resin composition and its molded article have high fluidity and melt tension, and are excellent in molding processability. B When the viscosity is 30.0 or less, the flowability and melt tension are excellent, and the polyolefin resin composition and its molded article can be prevented from decreasing in impact strength and from becoming poor in transparency.

[0027] In general, polyethylene is processed into industrial products by a molding method in which it goes through a molten state during film formation. In this process, the elongational flow properties represented by the above-mentioned extensional viscosity and strain hardening have a significant effect on the ease of formability. That is, polyethylene with a narrow molecular weight distribution and no long chain branching has poor moldability due to low melt strength, while polyethylene with ultra-high molecular weight components and long chain branching components has the property of strain hardening during melt elongation, that is, the elongational viscosity increases rapidly on the high strain side, and polyethylene that shows this property prominently has excellent moldability. Polyethylene resins with such elongational flow properties have the effect of preventing uneven thickness and blow-out of products in film molding, for example, and enabling high-speed molding, and thus have the advantage of improving the strength of molded products, but on the other hand, if the elongational flow properties are too strong, problems such as a decrease in the impact strength of the molded product due to strength anisotropy presumably caused by molecular orientation during molding, and a decrease in the surface smoothness of the molded product presumably caused by the property of too strong melt elasticity occur. In order to improve the molding process and overcome the disadvantages in the mechanical properties of the molded products caused by the extensional flow properties of polyethylene, by modifying the long chain branching structure, which is the main controlling factor of the extensional viscosity properties, extensive research was conducted on polyolefin resin compositions. As a result, a polypropylene resin was used and the extensional strain hardening rate [λmax(2.0)] was BIt has been found that when an ethylene polymer (B) having many long chain branching structures, such as those shown in the following formula (B-1), is used as the resin composition, it is possible to improve the molding processability as well as the mechanical properties, particularly the rigidity and impact strength. Furthermore, it has been found that when the long chain branching structure of the ethylene polymer (B) has a strain rate dependency of the elongation strain hardening degree that is different from that conventionally used and that is expressed by the following condition (B-7), it is possible to obtain an extremely excellent effect of improving all of the molding processability, mechanical properties, and transparency of the polyolefin resin composition.

[0028] Regarding the method of measuring the strain hardening degree, in principle, the same value can be obtained by any method as long as the uniaxial extensional viscosity can be measured. For example, the details of the measurement method and the measurement device are described in the publicly known document: Polymer 42 (2001) 8663. In measuring the ethylene polymer (B), preferred measuring methods and measuring instruments include the following.

[0029] Measurement method: Equipment: Rheometorics Ares Fixture: TA Instruments Extentional Viscosity Fixture ·Measurement temperature: 170℃ Distortion rate: 2 / sec Preparation of test specimen: Press mold a sheet of 18 mm x 10 mm and 0.7 mm thick.

[0030] Calculation method: The extensional viscosity at 170°C and a strain rate of 2 / sec is plotted on a double logarithmic graph with time t (sec) on the horizontal axis and extensional viscosity η (Pa·sec) on the vertical axis. On the double logarithmic graph, the maximum extensional viscosity until the strain amount reaches 4.0 after strain hardening is calculated as η Max (t1) (t1 is the time when the maximum elongational viscosity is shown), and the approximation line of the elongational viscosity before strain hardening is η Linear (t), then η Max (t1) / η LinearThe value calculated as (t1) is defined as the degree of strain hardening (λmax). The presence or absence of strain hardening is determined by whether or not there is an inflection point where the extensional viscosity changes from an upwardly convex curve to a downwardly convex curve with the passage of time. Figures 2 and 3 are typical plots of extensional viscosity. Figure 2 shows a case where an inflection point of extensional viscosity is observed, and η Max (t1), η Linear (t) is shown. Figure 3 shows the case where the inflection point of the extensional viscosity is not observed.

[0031] 2-7.Conditions (B-7) Furthermore, the ethylene polymer (B) component has a [λmax(2.0)] B and [λmax(0.1)], which was measured similarly with the extension strain rate set to 0.1 (unit 1 / s). B Ratio to [λmax(2.0)] B / [λmax(0.1)] B is, for example, 1.2 to 10.0, preferably 1.2 to 5.0, more preferably 1.3 to 4.0, and further preferably 1.3 to 3.0. This [λmax(2.0)] B / [λmax(0.1)] B The value of indicates the degree of development of the long chain branching structure in the ethylene polymer (B), and a higher value indicates a higher degree of development of the long chain branching structure, and a lower value indicates a lower degree of development of the long chain branching structure. [lambdamax(2.0)] B / [λmax(0.1)] B When [lambdamax(2.0)] is 1.2 or more, the ethylene polymer (B), the polyolefin resin composition and the molded article thereof are in a uniform melt state, and can have a thermally stable structure. In addition, the presence of a very long chain branch structure can prevent the molded article from having anisotropic strength, which can cause a decrease in impact strength and a decrease in transparency. B / [λmax(0.1)] B When the molecular weight ratio is 10.0 or less, the melt tension and flowability during molding are excellent, and the polyolefin resin composition and its molded article are prevented from decreasing in impact strength and from becoming poor in transparency.

[0032] 2-8.Conditions (B-8) Furthermore, the ethylene-based polymer (B) component is preferably a polymer produced by a polymerization reaction of ethylene using a catalyst containing a transition metal, more preferably a polymer produced by a polymerization reaction of ethylene using a catalyst containing a transition metal which will be described in detail later in the section 2-13. Production method of ethylene-based polymer (B), and even more preferably a polymer produced by a coordination anion polymerization reaction of ethylene using a catalyst containing a transition metal. Nowadays, various radical polymerization initiators are well known as transition metal-free ethylene polymerization catalysts. Specific examples include dialkyl peroxide compounds, alkyl hydroperoxide compounds, peroxides such as benzoyl peroxide and hydrogen peroxide, and azo compounds such as azobisisobutyronitrile and azobiscyclohexanecarbonitrile. Ethylene polymers produced by radical polymerization reactions using these radical polymerization initiators contain many long chain branched structures. When used as a component of a polyethylene resin composition, these polymers are effective in improving molding processability and transparency. However, the long chain branched structures become too numerous to be preferable, thereby lowering the strength of the composition and molded articles. Furthermore, these polymers are not preferable because they sufficiently lower the MFR of the ethylene polymer (B), sufficiently lower the density, or make it impossible to realize copolymerization with a preferred α-olefin, thereby failing to sufficiently improve the strength of the composition and molded articles. Incidentally, even if a catalyst contains a transition metal, if the polymerization reaction proceeds substantially by radical polymerization, such as in a so-called redox system, such as hydrogen peroxide / ferrous chloride or cerium salt / alcohol, it is not considered to be a catalyst containing a transition metal as defined in the present invention.

[0033] 2-9.Conditions (B-9) Furthermore, the ethylene polymer (B) component is further measured for a branching index (g) at a molecular weight of 1 million using a GPC measuring device that combines a differential refractometer, a viscosity detector, and a light scattering detector. C It is preferable that g' is 0.50 to 0.80. CThe g' value is an index showing the degree of development of the long chain branching structure in the ethylene polymer (B), and a higher value indicates a lower degree of development of the long chain branching structure, and a lower value indicates a higher degree of development of the long chain branching structure. C The value of g is more preferably 0.50 to 0.75, further preferably 0.55 to 0.70, and particularly preferably 0.55 to 0.65. C When the value is 0.80 or less, the effect of improving the molding processability of the polyolefin resin composition is enhanced, and the transparency of the resin composition and its molded article can be sufficiently ensured. C When the value is 0.50 or more, the molding processability of the polyolefin resin composition is improved, and the molded article can be prevented from having a lowered impact strength or a worsening of transparency. In the present invention, the g C 'Value or next term W C The value is an evaluation method of the amount of long chain branching using a molecular weight distribution curve and a branching index (g') calculated from the GPC-VIS measurement described below.

[0034] 2-10.Conditions (B-10) Furthermore, the ethylene polymer (B) component has a content (W ) of components having a molecular weight of 1,000,000 or more as measured by a GPC measuring device combining a differential refractometer, a viscosity detector, and a light scattering detector. C ) is preferably 0.01 to 30.0%. C The value is more preferably 0.01 to 10.0%, further preferably 0.02 to 8.0%, particularly preferably 0.05 to 6.0%, and most preferably 0.09 to 4.0%. W C When the value is 0.01% or more, the effect of improving the molding processability of the polyolefin resin composition is enhanced, and the transparency of the resin composition and its molded article can be sufficiently ensured. C When the value is 30.0% or less, the melt fluidity of the polyolefin resin composition can be prevented from becoming too low in its molding processability, which is convenient for the production and molding of the resin composition, and further, the impact strength of the molded body can be prevented from decreasing and the transparency can be prevented from deteriorating.

[0035] [Branch structure analysis using GPC-VIS] The GPC apparatus used was an Alliance GPCV2000 manufactured by Waters, equipped with a differential refractometer (RI) and a viscometer. The light scattering detector used was a multi-angle laser light scattering detector (MALLS) manufactured by Wyatt Technology, DAWN-E. The detectors were connected in the order of MALLS, RI, and viscometer. The mobile phase solvent was 1,2,4-trichlorobenzene (with the antioxidant Irganox1076 added at a concentration of 0.5 mg / mL). The flow rate was 1 mL / min. Two Tosoh GMHHR-H(S) HT columns were used in combination. The temperature of the column, sample injection section, and each detector was 140°C. The sample concentration was 1 mg / mL. The injection volume (sample loop volume) was 0.2175 mL. The absolute molecular weight (M), the radius of inertia (Rg) obtained from MALLS, and the intrinsic viscosity ([η]) obtained from Viscometer were calculated using the data processing software ASTRA (version 4.73.04) attached to MALLS, with reference to the following literature.

[0036] References: 1.Developments in polymer characterization, vol.4. Essex: Applied Science; 1984. Chapter1. 2.Polymer, 45, 6495-6505(2004) 3.Macromolecules, 33, 2424-2436(2000) 4.Macromolecules, 33, 6945-6952(2000)

[0037] [Branch index (g C Calculation of ') etc. The branching index (g') is calculated as the ratio (ηbranch / ηlin) of the intrinsic viscosity (ηbranch) obtained by measuring a sample with the above-mentioned Viscometer to the intrinsic viscosity (ηlin) obtained by separately measuring a linear polymer. When long chain branches are introduced into a polymer molecule, the radius of gyration becomes smaller compared to linear polymer molecules of the same molecular weight. Since the intrinsic viscosity decreases as the radius of gyration decreases, the ratio (ηbranch / ηlin) of the intrinsic viscosity of a branched polymer (ηbranch) to the intrinsic viscosity (ηlin) of a linear polymer of the same molecular weight decreases as more long chain branches are introduced. Therefore, when the branching index (g'=ηbranch / ηlin) is less than 1, it means that branches have been introduced, and as this value decreases, it means that the amount of long chain branches introduced increases. In particular, in the present invention, the absolute molecular weight obtained from MALLS is defined as the content ratio (%) of components with a molecular weight of 1 million or more to the total amount of components measured by RI, and the content (W C ) and the absolute molecular weight obtained from MALLS is calculated as g' at a molecular weight of 1 million, C The absolute molecular weight obtained from MALLS is calculated as g', and the minimum value of g' above in the molecular weight range of 100,000 to 1,000,000 is g C It is calculated as follows. Figures 4(a) and 4(b) show examples of the analysis results by the above GPC-VIS. Figure 4(a) shows the molecular weight distribution curve measured based on the molecular weight (M) obtained from MALLS and the concentration obtained from RI, and Figure 4(b) shows the branching index (g') at molecular weight (M). Here, linear polyethylene Standard Reference Material 1475a (National Institute of Standards & Technology) was used as the linear polymer.

[0038] 2-11.Conditions (B-11) Furthermore, the ethylene polymer (B) component has a ratio (X) of components eluted at 85°C or higher by temperature rising elution fractionation (TREF) of, for example, 2 to 15% by weight, preferably 3 to 14% by weight, and more preferably 4 to 13% by weight. When the X value is 15% by weight or less, the ratio of low-density components contained in the ethylene polymer (B) that effectively act to improve impact strength can be sufficiently ensured. When the X value is 2% by weight or more, a decrease in rigidity can be prevented.

[0039] Measurement of elution curves obtained by temperature rising elution fractionation (TREF) The dissolution curve of component (B) by TREF is measured as follows. Measurement equipment: A cross-fractionation device (Mitsubishi Chemical Corporation, product name CFC / T150A) is used as the measurement equipment, and the measurement is performed according to the measurement method in the attached operation manual. This cross-fractionation device is an equipment that connects online a temperature rising elution fractionation (TREF) mechanism that fractionates the sample by utilizing the difference in dissolution temperature, and a size exclusion chromatograph (SEC) that further fractionates the fractions by molecular size.

[0040] b. Sample solution: First, the sample to be measured (ethylene polymer (B)) is dissolved in a solvent (o-dichlorobenzene) at 140°C to a concentration of 4 mg / ml, and this is injected into the sample loop in the measuring device. The following measurements are performed automatically according to the set conditions.

[0041] c. Temperature-increasing elution fractionation: 0.4 ml of the sample solution held in the sample loop is injected into a TREF column (a stainless steel column with an internal diameter of 4 mm and a length of 150 mm, packed with glass beads, an inert carrier, attached to the device) that uses the difference in dissolution temperature for fractionation. The sample is cooled from 140°C to 0°C at a rate of 1°C / min and coated onto the inert carrier. At this time, a polymer layer is formed on the surface of the inert carrier in the order of highly crystalline components (easily crystallized) to less crystalline components (hardly crystallized). After the TREF column is held at 0°C for another 30 minutes, 2 ml of the components dissolved at 0°C are injected from the TREF column into a SEC column (3 columns, AD80M·S, manufactured by Showa Denko K.K.) at a flow rate of 1 ml / min. While the SEC is fractionating the molecules by size, the TREF column is heated to the next elution temperature (5°C) and held at that temperature for about 30 minutes. Measurements of each elution fraction in the SEC are performed at 39-minute intervals. The following temperatures are used as the elution temperatures, which are raised stepwise:

[0042] Elution temperature (℃): 0,5,10,15,20,25,30,35,40,45,49,52,55,58,61,64,67,70,73,76,79,82,85,88,91,94,97,100,102,120,140℃.

[0043] d. Drawing of elution curve: The absorbance proportional to the polymer concentration is measured with an infrared spectrophotometer attached to the device for the solution fractionated by molecular size in the SEC column (wavelength 3.42 μm, detected by methylene stretching vibration) to obtain a chromatogram for each elution temperature range. Using the built-in data processing software, the baseline of the chromatogram for each elution temperature range obtained in the above measurement is drawn and processed. The area of ​​each chromatogram is integrated to calculate an integral elution curve. In addition, this integral elution curve is differentiated by temperature to calculate a differential elution curve. The calculation results are plotted and output to a printer. The output differential elution curve is plotted on a scale of 89.3 mm per 100°C of elution temperature on the horizontal axis and 76.5 mm per 0.1 of the differential elution volume (amount of change per 1°C expressed as a fraction when the total integrated elution volume is set to 1.0) on the vertical axis.

[0044] e. Proportion (X) of components eluting at 85°C or higher: The amount of components eluting between 85°C and 140°C is X (unit: weight %).

[0045] 2-12. Composition of ethylene polymer (B) The ethylene-based polymer (B) is a copolymer of ethylene and an α-olefin having 3 to 18 carbon atoms. Examples of the α-olefin used as a copolymerization component include propylene, butene-1, 3-methylbutene-1, 3-methylpentene-1, 4-methylpentene-1, hexene-1, heptene-1, octene-1, decene-1, tetradecene-1, hexadecene-1, and octadecene-1. These α-olefins may be used alone or in combination of two or more. Among these, more preferred α-olefins are those having 3 to 10 carbon atoms, and specific examples thereof include propylene, butene-1, 3-methylbutene-1, 4-methylpentene-1, hexene-1, heptene-1, octene-1, and decene-1. More preferred α-olefins are those having 4 to 8 carbon atoms, and specific examples thereof include butene-1, 3-methylbutene-1, 4-methylpentene-1, hexene-1, heptene-1, and octene-1. Particularly preferred α-olefins are hexene-1 and octene-1, and most preferred are hexene-1 and octene-1. It is known that, even during ethylene homopolymerization, some of the olefin polymerization catalysts described below produce α-olefins such as 1-butene and hexene as by-products in the polymerization system due to ethylene oligomerization reaction, or a reaction called "Chain-walking reaction" in which short chain branches such as methyl groups and ethyl groups are produced in the olefin polymer main chain due to an isomerization reaction of the active center metal-terminal carbon bond at the olefin polymerization growth terminal, and the short chain branch structure in the ethylene homopolymer produced by these reactions may be indistinguishable from the short chain branch structure produced by copolymerization of α-olefins. Thus, in the present invention, ethylene homopolymer refers to a polymer resulting from polymerization carried out without externally supplying an α-olefin as a comonomer, and ethylene-α-olefin copolymer refers to a polymer resulting from polymerization carried out by externally supplying the α-olefin, and the term ethylene-based polymer is used collectively to refer to ethylene homopolymer and ethylene-α-olefin copolymer (including the cases where a comonomer other than an α-olefin as described below is used).

[0046] The ethylene polymer (B) used in the present invention is a copolymer mainly composed of ethylene, and the ratio of ethylene and α-olefin in the ethylene polymer (B) is, for example, about 75 to 99.5% by weight of ethylene and about 0.5 to 25% by weight of α-olefin, preferably about 78 to 97% by weight of ethylene and about 3 to 22% by weight of α-olefin, more preferably about 80 to 96% by weight of ethylene and about 4 to 20% by weight of α-olefin, and even more preferably about 82 to 95% by weight of ethylene and about 5 to 18% by weight of α-olefin. If the ethylene content is within this range, the polyolefin resin composition and its molded article have a good balance between rigidity and impact strength, and are also excellent in transparency.

[0047] Copolymerization may be any of alternating copolymerization, random copolymerization, and block copolymerization. Of course, it is also possible to use a small amount of comonomer other than ethylene or α-olefin, and in this case, examples of the comonomer include styrenes such as styrene, 4-methylstyrene, and 4-dimethylaminostyrene, dienes such as 1,4-butadiene, 1,5-hexadiene, 1,4-hexadiene, and 1,7-octadiene, cyclic compounds such as norbornene and cyclopentene, and oxygen-containing compounds such as hexenol, hexenoic acid, and methyl octenate. However, when dienes are used, they are preferably used within the range in which the long chain branch structure satisfies the above conditions (B-6) and (B-7).

[0048] 2-13. Production method of ethylene polymer (B) In the present invention, the ethylene polymer (B) requires the selection of an olefin polymerization catalyst suitable for imparting the ethylene polymer (B) with a molecular weight distribution and a long chain branching structure corresponding to the above conditions (B-3) to (B-5), and attention must be paid to adjusting the production conditions so as to satisfy (B-1) and (B-2).

[0049] As the olefin polymerization catalyst, a transition metal-containing olefin polymerization catalyst such as (i) a Ziegler catalyst, (ii) a metallocene catalyst, (iii) a Phillips catalyst, and (iv) a postmetallocene catalyst can be used. The ethylene polymer (B) is produced by contacting ethylene with the above-mentioned olefin polymerization catalysts (i) to (iv), more preferably (i), (ii), and (iv), still more preferably (i) and (ii), and particularly preferably (ii) metallocene catalyst, to polymerize or copolymerize ethylene. A plurality of olefin polymerization catalysts selected from (i) to (iv) may also be used.

[0050] Among the properties of the ethylene polymer (B) of the present invention, the properties represented by the above conditions (B-6) and (B-7), preferably the properties represented by the conditions (B-5), (B-6), (B-7) and (B-9), are considered to be derived from a characteristic long chain branching structure which is interpreted as containing an appropriate amount of sufficiently developed short long chain branches to such an extent that they can be entangled with each other at a level at which elongation strain hardening behavior is observed.

[0051] For example, as ethylene polymers having a long chain branching structure, as described above, those using Ziegler catalysts (for example, International Publication No. 97 / 10295, JP 2006-63325 A), those using complexes having bridged biscyclopentadienyl ligands, those using complexes having bridged bisindenyl ligands, those using complexes having bridged bisindenyl ligands in combination with non-MAO modified particles as catalysts, those using constrained geometry complex catalysts, and the like are known. In addition, examples of commercially available resins having a long chain branching structure include trade name: AFFINITY (registered trademark) FM1570 (manufactured by The Dow Chemical Company) and trade name: Excellen GMH (registered trademark) (manufactured by Sumitomo Chemical Co., Ltd.).

[0052] However, when an ethylene copolymer produced by the Ziegler catalyst is used, the molecular weight distribution and copolymer composition distribution become broad, the impact strength of the polyolefin resin composition and its molded article become insufficient, and the stickiness becomes severe due to the large amount of low crystallinity components, so that it cannot be said to be preferable. Furthermore, the catalyst produces only a small amount of long chain branched structures, so that the impact strength, etc. may not be sufficiently improved.

[0053] In addition, when an ethylene copolymer produced using a complex having a bridged biscyclopentadienyl ligand or a complex having a bridged bisindenyl ligand is used, the molecular weight distribution tends to broaden, so that the impact strength, etc. of the polyolefin resin composition and its molded article are insufficient, or the chain length of the long chain branch tends to be longer, so that the impact strength, etc. may not be sufficiently improved.

[0054] Furthermore, when an ethylene copolymer produced by combining a complex having a bridged bisindenyl ligand with non-MAO modified particles as a catalyst is used, the molecular weight distribution tends to be wider than that of the MAO cocatalyst, so the impact strength of the polyolefin resin composition and its molded product is insufficient. For example, the above-mentioned Excellen GMH, which is said to be a commercially available product actually produced using the catalyst, has a wide molecular weight distribution, long long chain branches, and an insufficient number of branches, so that the effect of improving molding processability is insufficient, and impact strength and transparency may not be sufficiently improved.

[0055] When an ethylene copolymer produced using a constrained geometry complex catalyst is used, for example, the above-mentioned AFFINITY (e.g., FM1570), which is said to be a commercially available product actually produced using the catalyst, has a long chain branch that is long and has an insufficient number of branches, and therefore is not preferable because it is insufficient in improving moldability and does not sufficiently improve impact strength or transparency.

[0056] In this situation, examples of suitable olefin polymerization catalysts for producing the ethylene polymer (B) used in the present invention having a characteristic molecular weight distribution and long chain branching structure include (a) a method of using a complex having a bridged (cyclopentadienyl)(indenyl) ligand or the like as an essential catalyst component, as discovered recently (JP Patent Publication No. 2011-137146, JP Patent Application No. 2010-268037, etc.), (b) a method of using a complex having a benzoindenyl ligand or the like as a catalyst component (JP Patent Publication No. 2006-2098, etc.), and (c) a method of using a bridged bis(indenyl)(cyclopentadienyl) ...cyclopentadienyl)(indenyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentadienyl)(cyclopentad and a method using a catalyst that uses a mixture of a complex having a bis(azulenyl) ligand, a bridged bis(cyclopentadienyl) ligand, and a borane compound or a borate compound that is a compound that generates an organoaluminum oxy compound and a cationic metallocene compound (Japanese Patent Application Laid-Open Nos. 2002-544296, 2005-507961, 2-276807, 2002-308933, 2004-292772, 8-311121, 8-311260, 8-48711, etc.).

[0057] Among preferred specific examples of the olefin polymerization catalyst which forms a long chain branched structure suitable for the ethylene polymer (B) used in the present invention, (a) a catalyst system having as an essential component a complex having a bridged (cyclopentadienyl)(indenyl) ligand or the like, and (c) a catalyst system using as a metallocene complex a complex having a bridged bis(indenyl) ligand or a bridged bis(cyclopentadienyl) ligand, and a mixture of an organoaluminum oxy compound and a borane compound or a borate compound which is a compound which forms a cationic metallocene compound, are more preferred, and (a) a catalyst system having as an essential component a complex having a bridged (cyclopentadienyl)(indenyl) ligand or the like is even more preferred. As an example, (a) a catalyst system containing as an essential component a complex having a bridging (cyclopentadienyl)(indenyl) ligand will be specifically described below.

[0058] (a) The olefin polymerization catalyst used in the present invention contains, as an essential component, a complex having a bridged (cyclopentadienyl)(indenyl) ligand or the like which forms a long-chain branched structure suitable for the ethylene polymer (B) of the present invention, and contains the following components (a-1) and (b), and further contains component (c) as desired. Component (a-1): A metallocene compound represented by the general formula (a-1-1) Component (b): A compound that reacts with the metallocene compound of component (a-1) to generate a cationic metallocene compound. Component (c): Microparticle carrier

[0059] i) Component (a-1) The component (a-1) is a metallocene compound represented by the following general formula (a-1-1).

[0060] [ka]

[0061] [In formula (a-1-1), M represents a transition metal selected from the group consisting of Ti, Zr, and Hf. X 1 and X 2Q each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a hydrocarbon group having 1 to 20 carbon atoms containing an oxygen atom or a nitrogen atom, an amino group substituted with a hydrocarbon group having 1 to 20 carbon atoms, or an alkoxy group having 1 to 20 carbon atoms. 1 and Q 2 R each independently represents a carbon atom, a silicon atom, or a germanium atom. 1 each independently represents a hydrogen atom or a hydrocarbon group having 1 to 10 carbon atoms; 1 At least two of them combine to form Q 1 and Q 2 m is 0 or 1, and when m is 0, Q 1 is R 2 and R 3 It is directly bonded to a conjugated five-membered ring containing R 2 each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing hydrocarbon group having 1 to 18 carbon atoms and containing 1 to 6 silicon atoms, a halogen-containing hydrocarbon group having 1 to 20 carbon atoms, a hydrocarbon group having 1 to 20 carbon atoms containing an oxygen atom, or a hydrocarbon-substituted silyl group having 1 to 20 carbon atoms; 2 Even if R is a hydrocarbon group, 4 It does not form a ring with the carbon atom to which it is attached, like R 3 R represents a saturated or unsaturated divalent hydrocarbon group having 4 or 5 carbon atoms that forms a condensed ring with the 5-membered ring to which it is bonded. 4 is R 3 Each of n is independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing hydrocarbon group having 1 to 18 carbon atoms and containing 1 to 6 silicon atoms, a halogen-containing hydrocarbon group having 1 to 20 carbon atoms, or a hydrocarbon-substituted silyl group having 1 to 20 carbon atoms. n is an integer of 0 to 10, and when n is 2 or more, R 4 At least two of R may form a ring together with the carbon atom to which they are attached. 5each independently represents a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing hydrocarbon group having 1 to 18 carbon atoms and containing 1 to 6 silicon atoms, a halogen atom-containing hydrocarbon group having 1 to 20 carbon atoms, a hydrocarbon group having 1 to 20 carbon atoms and containing an oxygen atom, or a hydrocarbon group-substituted silyl group having 1 to 20 carbon atoms, 5 Even if R is a hydrocarbon group, etc. 4 It does not form a ring with the carbon atom to which it is attached, such as:

[0062] Among the specific compounds exemplified above, particularly preferred metallocene compounds as component (a-1) are shown below. Dimethylsilylene(cyclopentadienyl)(indenyl)zirconium dichloride, isopropylidene(cyclopentadienyl)(indenyl)zirconium dichloride, dimethylsilylene(cyclopentadienyl)(3-methylindenyl)zirconium dichloride, dimethylsilylene(cyclopentadienyl)(3-phenylindenyl)zirconium dichloride, dimethylsilylene(cyclopentadienyl)(4-phenylindenyl)zirconium dichloride, dimethylsilylene(cyclopentadienyl)(benzo[e]indenyl)zirconium dichloride, isopropylidene(cyclopentadienyl)(3-methylindenyl)zirconium dichloride, dimethylsilylene(cyclopentadienyl)(3-t-butylindenyl)zirconium dichloride, isopropylidene(cyclopentadienyl)(3-t-butylindenyl)zirconium dichloride Indenyl) zirconium dichloride, dimethylgermylene (cyclopentadienyl) (indenyl) zirconium dichloride, cyclobutylidene (cyclopentadienyl) (3-t-butylindenyl) zirconium dichloride, dimethylsilylene (cyclopentadienyl) (indenyl) hafnium dichloride, dimethylsilylene (cyclopentadienyl) (3-methylindenyl) hafnium dichloride, dimethylsilylene (cyclopentadienyl) (3-t-butylindenyl) hafnium dichloride, dimethylsilylene (4-t-butylcyclopentadienyl) (indenyl) zirconium dichloride, dimethylsilylene (4-t-butylcyclopentadienyl) (indenyl) zirconium dichloride, dimethylsilylene (4-t-butylcyclopentadienyl) (indenyl) zirconium dimethyl, and the like.

[0063] ii) Component (b) The olefin polymerization catalyst exemplified as an olefin polymerization catalyst containing, as an essential component, a complex having a bridged (cyclopentadienyl)(indenyl) ligand or the like which forms a long-chain branched structure suitable for the ethylene polymer (B) used in the present invention, contains, in addition to the above-mentioned component (a-1), a compound (component (b), hereinafter sometimes simply referred to as b) which reacts with the metallocene compound of component (a-1) (component (a-1), hereinafter sometimes simply referred to as a) to form a cationic metallocene compound.

[0064] One example of the compound (b) which reacts with the metallocene compound (a) to form a cationic metallocene compound is an organoaluminum oxy compound. The organoaluminum oxy-compound has an Al-O-Al bond in the molecule, and the number of bonds is usually in the range of 1 to 100, preferably 1 to 50. Such an organoaluminum oxy-compound is usually a product obtained by reacting an organoaluminum compound with water. Among the above-mentioned organoaluminum oxy compounds, those obtained by reacting alkylaluminum with water are usually called aluminoxanes, and in particular, methylaluminoxane (including those essentially consisting of methylaluminoxane (MAO)) is a suitable organoaluminum oxy compound.

[0065] Other specific examples of the compound (b) that reacts with the metallocene compound (a) to form a cationic metallocene compound include borane compounds and borate compounds. More specifically, the borane compound may be triphenylborane, tri(o-tolyl)borane, tri(p-tolyl)borane, tri(m-tolyl)borane, tri(o-fluorophenyl)borane, tris(p-fluorophenyl)borane, tris(m-fluorophenyl)borane, tris(2,5-difluorophenyl)borane, tris(3,5-difluorophenyl)borane, tris(4-trifluoromethylphenyl)borane, tris(3,5-ditrifluoromethylphenyl)borane, tris(2,6-ditrifluoromethylphenyl)borane, tris(pentafluorophenyl)borane, tris(perfluoronaphthyl)borane, tris(perfluorobiphenyl), tris(perfluoroanthryl)borane, tris(perfluorobinaphthyl)borane, and the like.

[0066] iii) component (c) The olefin polymerization catalyst exemplified as an essential component of the olefin polymerization catalyst having a bridged (cyclopentadienyl)(indenyl) ligand or the like that forms a long-chain branched structure suitable for the ethylene polymer (B) used in the present invention preferably contains a fine particle support (component (c), hereinafter sometimes simply referred to as c).

[0067] The particulate carrier, component (c), may be an inorganic carrier, a particulate polymer carrier, or a mixture thereof. The inorganic carrier may be a metal, a metal oxide, a metal chloride, a metal carbonate, a carbonaceous material, or a mixture thereof. Suitable metals that can be used in the inorganic support include, for example, iron, aluminum, nickel, and the like.

[0068] Furthermore, examples of metal oxides include single oxides or composite oxides of elements in Groups 1 to 14 of the periodic table. Examples of such metal oxides include various natural or synthetic single oxides or composite oxides such as SiO2, Al2O3, MgO, CaO, B2O3, TiO2, ZrO2, Fe2O3, Al2O3·MgO, Al2O3·CaO, Al2O3·SiO2, Al2O3·MgO·CaO, Al2O3·MgO·SiO2, Al2O3·CuO, Al2O3·Fe2O3, Al2O3·NiO, and SiO2·MgO. Here, the above formula is not a molecular formula but represents only the composition, and the structure and component ratio of the composite oxide used in the present invention are not particularly limited. Furthermore, the metal oxide used in the present invention may absorb a small amount of moisture and may contain a small amount of impurities.

[0069] As the metal chloride, for example, chlorides of alkali metals and alkaline earth metals are preferable, and specifically, MgCl2, CaCl2, etc. are particularly suitable. As the metal carbonate, alkali metal or alkaline earth metal carbonate is preferable, and specific examples thereof include magnesium carbonate, calcium carbonate, barium carbonate, and the like. Examples of the carbonaceous material include carbon black and activated carbon. Any of the above inorganic carriers can be suitably used in the present invention, with metal oxides, silica, alumina and the like being particularly preferred.

[0070] As described above, the organoaluminum oxy-compound or the like is used as the component (b) together with the component (a-1). In this case as well, it is preferable to use the borane compound or borate compound in combination with the organoaluminum oxy-compound in order to further enhance the desired long chain branched structure properties of the ethylene polymer (B) of the present invention. Similarly, it is also preferable to contain the component (c) in addition to the components (a-1) and (b).

[0071] In the present invention, when polymerizing or copolymerizing ethylene, it is needless to say that it is necessary to optimize various conditions such as polymerization method, ethylene raw material, polymerization medium, polymerization temperature, polymerization process, scavenger, etc., taking into consideration various properties desired for the ethylene polymer (B) and the properties of the olefin polymerization catalyst used. For example, when an ethylene polymer (B) with a lower MFR and lower density is desired, the chain transfer agent concentration is set to a lower value, the α-olefin concentration is set to a higher value, various operating temperatures are set to a lower value corresponding to the melting temperature of the polymer in order to prevent problems such as fixation and blockage of the polymer in the production process, a low molecular weight hydrocarbon solvent such as propane or butane in which the polymer is less likely to dissolve is selected in slurry polymerization, gas phase polymerization without using a solvent is selected, or solution polymerization in which the polymer is handled in a dissolved state is selected. In addition, when it is desired to impart significant long chain branching properties, it is preferable to actively select low monomer concentration conditions, high polymer concentration conditions, low scavenger concentration conditions, high temperature polymerization conditions, long-term polymerization conditions, etc. so as to promote chain transfer reactions other than with hydrogen. Specifically, when an ethylene polymer (B) having a lower MFR (i.e., a higher molecular weight) is desired, the hydrogen concentration during the reaction can be reduced, and when an ethylene polymer (B) having a lower density is desired, the comonomer content can be increased.

[0072] 3. Component (C) Nucleating Agent For the purpose of improving the transparency of the component (A) and improving the rigidity and heat resistance, it is more preferable to compound one or more substances (nucleating agents) having a nucleating effect on polypropylene resins as component (C) in an amount of 0.03 to 2% by weight based on the total amount of the composition. If the compounding amount is 0.03% by weight or more, a sufficient effect can be obtained, and if the compounding amount is 2% by weight or less, the adverse effects caused by the use of the nucleating agent can be prevented. If the compounding amount is more than 2% by weight, it is excessive and not only uneconomical but also there is a risk of adverse effects such as a decrease in transparency and smoke or odor during sheet molding. The nucleating agent may be added to the resin composition in a state of being masterbatched in advance with the same component as component (A) or component (B), or with another component belonging to component (A) or component (B), or with another resin component (D) other than component (A) or component (B). When the other resin component (D) is used as a resin material for making a master batch, the content of the resin component (D) in the resin composition is 0.03 to 20% by weight, and preferably 0.1 to 10% by weight (wherein the total amount of components (A), (B), (C) and (D) is taken as 100% by weight). Examples of nucleating agents include the following substances: (C1) Aluminum-di-para-tert-butyl-hydroxybenzoic acid represented by the following formula [1] (C2) Sodium 2,2-methylenebis(2,6-di-tert-butylphenyl)phosphate represented by the following formula [2] (C3) A basic polyvalent metal salt of a cyclic organic phosphate represented by the following formula [3]: (C4) A sorbitol-based compound represented by the following formula [4] (C5) Metal salts of rosins

[0073] [ka]

[0074] In the above formula [3], R 1 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and R 2 and R 3are hydrogen atoms or alkyl groups having 1 to 12 carbon atoms, and may be different from each other; M is a metal atom of Group III or IV of the periodic table; and X is a hydroxyl group having a number two less than the valence of the metal. 4 and R 5 is a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, and may be different from each other. The nucleating agents exemplified here are representative, and substances other than the exemplified ones may be used as long as they have the same effect, and such substances may be contained in the necessary amount at the time of final molding into a sheet, and any method may be used for blending. The (C5) metal salts of rosins are obtained by metal-modifying rosins (known as rosin), which are a type of natural resin obtained from plants, and are commercially available products, for example, from Arakawa Chemical Industries Co., Ltd.

[0075] 4. Combination of ingredients (A) and (B) The polyolefin resin composition of the present invention contains the above-mentioned components (A) and (B), and the blending ratios of components (A) and (B) in the polyolefin resin composition of the present invention are 50-90% by weight and 50-10% by weight, and preferably 70-80% by weight and 30-20% by weight. If the blending ratios of components (A) and (B) are within the above-specified ranges, the polyolefin resin composition is excellent in cold impact resistance, rigidity, transparency, and thermoformability. On the other hand, if the amount of component (B) is greater than the above-specified ranges, the rigidity is inferior, and if the amount is less than the above-specified ranges, the impact resistance and thermoformability are inferior.

[0076] 5. Other Ingredients In the present invention, the polyolefin resin composition, which is the resin material forming the sheet, may contain, in addition to the above-mentioned components (A), (B) and (C), auxiliary additives generally used in polyolefins, such as antioxidants, neutralizing agents, heat stabilizers, light stabilizers, UV absorbers, antistatic agents, antifogging agents, slip agents, antiblocking agents, antibacterial agents, colorants, etc. Also, within the range that does not impair the characteristics of the present invention, a rubber component consisting of two or more α-olefins having 2 to 8 carbon atoms may be compounded.

[0077] 6. Formation of polyolefin resin composition The polyolefin resin composition may be prepared by dry blending the above-mentioned components as necessary and directly supplying them to a sheet manufacturing apparatus to form a sheet, or may be prepared by melt-kneading the components using an extruder, Banbury mixer, kneader-ruder, etc. before supplying them to the sheet manufacturing apparatus, or may be further solidified and formed into granules of an appropriate size and then supplied to the sheet manufacturing apparatus. In other words, as long as the blending amount of each component in the finally obtained sheet molding is within the above-mentioned range and the mixed state is practically problem-free, any blending method or process for each component forming the polyolefin resin composition may be used.

[0078] 7. Seats and their manufacture The sheet of the present invention is a single-layer or multi-layer sheet having at least one layer made of the above-mentioned polyolefin resin composition of the present invention. The sheet of the present invention can be produced by any known molding method, but in order to utilize the features of the present invention, a method that can make both surfaces or one side of the sheet smooth and glossy is preferable. Specifically, the method of continuously producing a sheet includes a method of extruding a molten resin material into a flat plate shape, and continuously cooling and solidifying the surface while sandwiching it between a pair of rotating rolls with smooth surfaces, a method of using one or two belts with smooth surfaces instead of rolls, a method of once solidifying into a flat plate shape regardless of the smoothness of the surface, and then pressing a roll or belt with a smooth surface to finally obtain a sheet with a smooth surface, and a method of extruding a molten resin material into a cylindrical shape and cooling and solidifying it with a water flow or air flow from the surroundings. In addition, the method of discontinuously producing the sheet includes a method of placing a sheet with an uneven surface that has been once flattened by some method between a pair of smooth-surfaced plates, pressing the plates together while applying heat to make the surface smooth, and a method of supplying a molten resin material between a pair of smooth-surfaced plates and cooling and solidifying it while applying pressure with the plates. Of the above-mentioned production methods, from the standpoint of quality stability and productivity, the method of continuous molding with a roll or steel belt having a smooth surface is preferred, and the method of pressing down with a steel belt from one or both sides is particularly preferred.

[0079] 8.Laminated Sheet As described above, the sheet of the present invention may be a single-layer sheet or a multi-layer sheet, so long as it has a layer made of the polyolefin resin composition of the present invention. As a method for obtaining a multi-layer laminated sheet having a layer made of the polyolefin resin composition, any method that has been used in the past for polypropylene resins can be used. Specifically, in the above-mentioned sheet forming process, a layer made of the polyolefin resin composition and a layer made of a desired material are laminated in a molten state, optionally via an adhesive resin, and then cooled and solidified to obtain a sheet, so-called co-extrusion method, a lamination method in which sheets are once formed and bonded together with a molten resin or adhesive, a thermal lamination method or extrusion coating method in which one sheet is laminated on the other in a molten state and then immediately cooled and solidified to obtain a laminated sheet, and the like can be mentioned. The sheet of the present invention can be applied to all fields, in which the performance can be improved by replacing the polypropylene resin layer in all laminates in which polypropylene resin has been used in the past.

[0080] 9.Applications The sheet of the present invention is excellent in transparency, rigidity, cold impact resistance, and thermoformability, and the thermoformed products obtained from it are also excellent in transparency, rigidity, cold impact resistance, and thermoformability, and further, the molded products obtained by the solid-phase molding method or the compressed air molding method are excellent in transparency, rigidity, cold impact resistance, thermoformability, and gloss. Therefore, it can be used for the following applications.

[0081] Packaging containers etc. Packaging containers are often required to have a high level of transparency, and therefore the more transparent they are, the better. However, conventional polypropylene sheets have limited impact resistance, and none of them can be used for freezing, for example. On the other hand, packaging containers are inevitably required to have the ability to withstand drops, tumbling, and impacts during transportation, maintain their sealability, and protect the contents, so the higher the impact resistance, the better, but conventional technologies have had no choice but to sacrifice transparency. In the food industry, heat resistance is required to withstand heating and cooking using microwave ovens, boiling, retort processing, and other heat sterilization processes, but conventionally it has not been possible to simultaneously obtain sufficient transparency and impact resistance. Naturally, the higher the rigidity, the better, and even if both transparency and impact resistance are achieved at the expense of rigidity, the practical use of the material as a packaging material will be impaired. The present invention solves all of these problems at the same time, and is suitable for packaging material applications such as containers, lids, and trays. Furthermore, when used as a packaging container, a process known as thermoforming is often carried out in which the sheet is heated to a molten or semi-molten state, then pressed against a mold by air pressure or the like, and cooled and solidified to obtain a molded product of the desired shape. The sheet of the present invention is easy to mold because it is less likely to sag due to its own weight when heated, and there is almost no deterioration in transparency even after the thermoforming process. Therefore, it has the advantage that thermoformed products with excellent transparency can be obtained quickly and in high yields, and it can be said that the sheet is extremely suitable for use as a packaging container sheet.

[0082] 10. Molded products The molded article of the present invention is obtained from the sheet of the present invention and has excellent transparency, rigidity, cold impact resistance, and thermoformability. Specifically, it is suitable as a packaging material for containers, lids, trays, etc.

[0083] 11. Modifier for polypropylene resin The polypropylene resin modifier of the present invention contains the polyethylene resin of component (B) described above. The polyethylene resin of component (B) is excellent in improving the molding processability of polypropylene resin and is also moderately excellent in improving the balance between impact strength and rigidity, making it suitable as a polypropylene resin modifier. The blending ratio of the polypropylene resin modifier of the present invention to the polypropylene resin is preferably polypropylene resin:modifier 50-90% by weight:50-10% by weight, more preferably 70-80% by weight:30-20% by weight. The polypropylene resin modifier of the present invention may be dry-blended with a polypropylene resin and components added as necessary, and directly supplied to a sheet manufacturing apparatus to be molded into a sheet, or may be melt-kneaded with a polypropylene resin using an extruder, Banbury mixer, kneader-ruder, etc. before being supplied to the sheet manufacturing apparatus, or the melt-kneaded product may be solidified and formed into granules of an appropriate size, and these may be supplied to the sheet manufacturing apparatus. In other words, as long as the mixture is in a practically acceptable state, any method or process for blending each component that forms the polyolefin resin composition may be used. EXAMPLES

[0084] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The following examples and comparative examples were evaluated by the following methods.

[0085] I. Resin property evaluation method (1) MFR (Melt Flow Rate) The MFR of component (A) was measured according to JIS-K6758 "Testing method for polypropylene" for melt flow rate (temperature 230°C, load 2.16 kgf). The MFR of component (B) was measured according to JIS-K7210 "Testing method for flow of thermoplastics" for test condition 4 (temperature 190°C, load 2.16 kgf).

[0086] (2) Density measurement method The density of component (B) was measured by hot pressing the pellets to prepare a 2 mm thick pressed sheet, placing the sheet in a 1000 ml beaker, filling it with distilled water, covering it with a watch glass, and heating it with a mantle heater. After boiling the distilled water for 60 minutes, the beaker was placed on a wooden stand and allowed to cool. At this time, the boiled distilled water after boiling for 60 minutes was 500 ml, and the time until it reached room temperature was adjusted to not less than 60 minutes. In addition, the test sheet was immersed in the water at approximately the center so as not to come into contact with the beaker or the water surface. After annealing the sheet for 16 to 24 hours under conditions of 23°C and 50% humidity, it was punched out to 2 mm in length and width, and measured at a test temperature of 23°C in accordance with JIS K7112 "Method of measuring density and specific gravity of plastics - non-foamed plastics".

[0087] (3) Gel Permeation Chromatography (GPC) Method The molecular weight distributions Mw / Mn and Mz / Mw of component (B) were determined by gel permeation chromatography (GPC). The conversion from retention volume to molecular weight was performed using a calibration curve prepared in advance using standard polystyrenes. The standard polystyrenes used were the following brands manufactured by Tosoh Corporation: F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, and A1000. A calibration curve was created by injecting 0.2 mL of a solution dissolved in ODCB (containing 0.5 mg / mL BHT) so that each was 0.5 mg / mL. A cubic equation obtained by approximating with the least squares method was used for the calibration curve. A general-purpose calibration curve was used for conversion to molecular weight, based on "Size Exclusion Chromatography" by Mori Sadao (Kyoritsu Shuppan). The viscosity equation used in this case was [η] = K × M α The following values ​​were used: PS:K = 1.38 x 10 -4 , α=0.7 PE:K = 3.92 x 10 -4 , α=0.733

[0088] The GPC measurement conditions are as follows: Apparatus: Waters GPC (ALC / GPC 150C) Detector: FOXBORO MIRAN 1A IR detector (measurement wavelength: 3.42 μm) Column: Showa Denko AD806M / S (3 columns) Mobile phase solvent: o-dichlorobenzene Measurement temperature: 140℃ Flow rate: 1.0ml / min Injection amount: 0.2ml Sample preparation: Prepare a 1 mg / mL solution of the sample using ODCB (containing 0.5 mg / mL BHT) and dissolve the sample at 140° C. for approximately 1 hour. The baseline and intervals of the obtained chromatogram were as shown in FIG.

[0089] (4) Branching index (gc) The minimum value (gc) of the branching index g' measured by a GPC measuring device combining a differential refractometer, a viscosity detector and a light scattering detector was determined within the molecular weight range of 100,000 to 1,000,000. [Branch structure analysis using GPC-VIS] The GPC apparatus used was an Alliance GPCV2000 manufactured by Waters, equipped with a differential refractometer (RI) and a viscometer. The light scattering detector used was a multi-angle laser light scattering detector (MALLS) manufactured by Wyatt Technology, DAWN-E. The detectors were connected in the order of MALLS, RI, and viscometer. The mobile phase solvent was 1,2,4-trichlorobenzene (with the antioxidant Irganox1076 added at a concentration of 0.5 mg / mL). The flow rate was 1 mL / min. Two Tosoh GMHHR-H(S) HT columns were used in combination. The temperature of the column, sample injection section, and each detector was 140°C. The sample concentration was 1 mg / mL. The injection volume (sample loop volume) was 0.2175 mL. The absolute molecular weight (M), the radius of inertia (Rg) obtained from MALLS, and the intrinsic viscosity ([η]) obtained from the Viscometer were calculated using the data processing software ASTRA (version 4.73.04) attached to MALLS, with reference to the above-mentioned literature. [Branch index (g C ) etc.] The branching index (g') was calculated as the ratio (ηbranch / ηlin) of the intrinsic viscosity (ηbranch) obtained by measuring the sample with the above-mentioned Viscometer to the intrinsic viscosity (ηlin) obtained by separately measuring a linear polymer. The absolute molecular weight obtained from MALLS is the minimum value of g' above in the range of molecular weight from 100,000 to 1,000,000. C Here, linear polyethylene Standard Reference Material 1475a (National Institute of Standards & Technology) was used as the linear polymer.

[0090] (4) Measurement of elution curves obtained by temperature rising elution fractionation (TREF) The dissolution curve of component (B) by TREF was measured as follows. Measurement equipment: A cross-fractionation device (Mitsubishi Chemical Corporation, product name CFC / T150A) was used as the measurement equipment, and measurements were performed according to the measurement method in the attached operation manual. This cross-fractionation device is an online device that combines a temperature rising elution fractionation (TREF) mechanism that fractionates samples by utilizing differences in dissolution temperature with a size exclusion chromatograph (SEC) that further fractionates the fractions by molecular size.

[0091] b. Sample solution: First, the sample to be measured (ethylene-α-olefin copolymer) was dissolved in a solvent (o-dichlorobenzene) at 140°C to a concentration of 4mg / ml, and this was injected into the sample loop in the measuring device. The following measurements were performed automatically according to the set conditions.

[0092] c. Temperature-increasing elution fractionation: 0.4 ml of the sample solution held in the sample loop was injected into a TREF column (a stainless steel column with an internal diameter of 4 mm and a length of 150 mm, packed with glass beads as an inert carrier, attached to the device) that fractionates by utilizing the difference in dissolution temperature. The sample was cooled from 140°C to 0°C at a rate of 1°C / min and coated onto the inert carrier. At this time, a polymer layer was formed on the surface of the inert carrier in the order of highly crystalline components (easily crystallized) to less crystalline components (hardly crystallized). After the TREF column was held at 0°C for another 30 minutes, 2 ml of the components dissolved at 0°C were injected from the TREF column into a SEC column (3 columns, AD80M·S, manufactured by Showa Denko K.K.) at a flow rate of 1 ml / min. While the molecular size fractionation was being carried out by the SEC, the temperature of the TREF column was raised to the next elution temperature (5°C) and held at that temperature for about 30 minutes. Measurements of each elution fraction by the SEC were carried out at 39-minute intervals. The following temperatures were used as elution temperatures, which were increased stepwise:

[0093] Elution temperature (℃): 0,5,10,15,20,25,30,35,40,45,49,52,55,58,61,64,67,70,73,76,79,82,85,88,91,94,97,100,102,120,140℃.

[0094] d. Drawing of elution curve: The absorbance proportional to the polymer concentration was measured with an infrared spectrophotometer attached to the device for the solution fractionated by molecular size in the SEC column (wavelength 3.42 μm, detected by methylene stretching vibration), and a chromatogram was obtained for each elution temperature range. Using the built-in data processing software, the baseline of the chromatogram for each elution temperature range obtained in the above measurement was drawn and processed. The area of ​​each chromatogram was integrated to calculate an integral elution curve. In addition, this integral elution curve was differentiated by temperature to calculate a differential elution curve. The calculation results were plotted and output to a printer. The output differential elution curve was plotted on a scale of 89.3 mm per 100°C elution temperature on the horizontal axis and 76.5 mm per 0.1 differential elution volume (amount of change per 1°C expressed as a fraction when the total integrated elution volume is 1.0) on the vertical axis.

[0095] e. Proportion (X) of component eluted at 85° C. or higher: the amount of component eluted between 85° C. and 140° C. was designated as X (unit: weight %).

[0096] (5) Melt tension Using a Toyo Seiki Co., Ltd. Capillograph, the resin that had been heated and stabilized at 230°C in a furnace was extruded from an orifice with an inner diameter of 2.095 mm and a length of 8 mm at a piston speed of 1 cm / min, and the extruded molten resin was pulled at a speed of 4 m / min to measure the tension applied to the pulley that passed through, and this was recorded as the melt tension value (unit: mN).

[0097] II. Sheet physical property evaluation method (1) Transparency (haze: haze value) Using the sheet obtained by the method described below, measurements were made in accordance with JIS-K7105 "Testing methods for optical properties of plastics." The judgment criteria are based on the measured haze value (unit: %) and are as follows: ◎: Less than 15 ○: 15 to less than 25 △: 25~35 ×:35 or more +: slightly better than other products with the same rating

[0098] (2) Rigidity (flexural modulus) Using a sheet obtained by the method described below, measurements were performed in accordance with JIS-K6758 "Testing Method for Polypropylene." The criteria for judgment were based on the measured value of the flexural modulus (unit: MPa), as follows: ◎: 1300 or more ○: Less than 1300 to 1100 △: Less than 1100 to 1000 ×: Less than 1000 +: slightly better than other products with the same rating

[0099] (3) Impact resistance (impact core test) The sheets obtained by the method described below were used to evaluate impact resistance at 23° C. according to the following method.

[0100] Impact test: The test piece is sandwiched between a circular impact core stand with a concave portion of 16.2 cmD in diameter and a hemispherical impact core with a tip of 15.8 mmD in diameter. A weight set at any height is dropped onto the top of the impact core to confirm the state of destruction of the test piece. The height at which the weight is dropped is gradually changed, and the energy at which the probability of destruction is 50% is calculated using a specified formula based on the relationship between the height and the destruction frequency, and this destruction energy value is the falling ball impact strength defined in this test method. b. Temperature adjustment of the test piece: The test piece is conditioned in a thermostatic chamber adjusted to the specified temperature for at least 30 minutes, and at the time of testing, it is quickly removed from the chamber and a weight is dropped on it within 5 seconds.

[0101] c. Calculation: Calculate the 50% fracture energy (E) using the following formula. E = [HS(T / 100-1 / 2)] × W × 0.098 E: 50% breaking energy (J) H: Minimum height at which all test pieces (5 pieces) break (cm) S: Height interval during repeated testing (cm) T: The sum of the failure rates (percentages) of the five test pieces at each test load W: Fall load (cm)

[0102] The criteria are based on the measured value of 50% fracture energy (unit: J) and are as follows: ◎: 15 or more ○: Less than 15 to 10 △: Less than 10 to 5 ×: Less than 5 +: slightly better than other products with the same rating

[0103] (4) Low temperature impact resistance The measurement temperature was set to -20°C, and the impact core test was carried out in the same manner as described above to evaluate the low-temperature drop impact strength. The criteria are based on the measured value of 50% fracture energy (unit: J) and are as follows: ◎: 7 or more ○: Less than 7 to 3 ×: Less than 3 +: slightly better than other products with the same rating

[0104] (5) Formability The melt tension value (unit: mN) of the polyolefin resin composition was measured according to the above-mentioned method, and the moldability was evaluated according to the following criteria. ◎: 20 or more ○: Less than 20 to 15 △: Less than 15 to 10 ×: Less than 10 +: slightly better than other products with the same rating

[0105] III. Sheet Forming The sheets used in the above evaluations were molded using the following equipment and under the following molding conditions. (1) Equipment: Three-roll polishing sheet forming machine manufactured by Plagiken Co., Ltd. Basic configuration: Single-screw extruder (40φ·L / D=28·2 units used) / feed block / coat hanger die / metal polishing 3-roll take-up machine / winder Basic configuration: Single-screw extruder (40φ·L / D=28·2 units used) / feed block / coat hanger die / metal polishing 3-roll take-up machine / winder

[0106] (2) Conditions: a. Raw material preparation: Component (A) and component (B) were mixed by dry blending, and the mixture was fed to the extruder of a sheet molding machine, where the two components were melt-kneaded and molded into a sheet. When component (C) was added, it was melt-kneaded with component (A) beforehand. Standard amounts of antioxidants and neutralizers were added in all of the examples and comparative examples described below. b. Extrusion temperature setting: The extruder was set at 190°C at the most upstream, and gradually increased the temperature until the tip was set at 230°C. After that, the connecting pipes, feed block, and die were all set at 230°C. c. Lip opening: The die lip opening was 0.8 mm. d. Air gap: The distance from the tip of the die lip to the roll was 150 mm. e. Take-off machine: The molten resin was cooled and solidified using a take-off machine with three metal polishing (mirror finish) rolls arranged vertically in series. The inside of the rolls was designed to be cooled by circulating oil at a constant temperature, and the oil temperature at this time was all 60°C. The roll diameter was 30 cm. The gap between the rolls was 0.5 mm. f. Drawing speed: All molding was performed at 3 m / min to obtain sheets with a thickness of 0.30 mm.

[0107] IV. Material (1) Component (A) Polypropylene resin Propylene homopolymer: Homo PP (PP-H) manufactured by Japan Polypropylene Corporation, FY6 (MFR: 2.5g / 10min) by Novatec PP

[0108] (2) Component (B) Polyethylene resin LCB: Ethylene-hexene copolymer produced according to the following production example. LD (LF122): High-pressure low-density polyethylene (LDPE: manufactured by Japan Polyethylene Co., Ltd., product name: Novatec LD·LF122, MFR: 0.3g / 10min, density: 0.923g / cm 3 ) LL (UF230): Ethylene-butene copolymer (manufactured by Japan Polyethylene Co., Ltd., product name: Novatec LL UF230, MFR: 1.1 g / 10 min, density: 0.921 g / cm 3 ) HD (HB530): High density polyethylene (HDPE: manufactured by Japan Polyethylene Co., Ltd., product name: Novatec HD HB530, MFR: 0.3g / 10min, density: 0.964g / cm 3 ) LL (KS260): Ethylene-hexene copolymer (manufactured by Japan Polyethylene Co., Ltd., product name Kernel KS260, MFR: 2.2 g / 10 min, density: 0.902 g / cm 3 )

[0109] Example of LCB manufacturing (1) Synthesis of olefin polymerization catalysts; In a nitrogen atmosphere, 30 grams of silica calcined at 400°C for 5 hours was placed in a 500ml three-neck flask, and then 195ml of dehydrated toluene was added to make a slurry. In a separately prepared 200ml two-neck flask, 820 milligrams of dimethylsilylene (4-(4-trimethylsilyl-phenyl)-indenyl) (cyclopentadienyl) zirconium dichloride synthesized according to the method described in International Publication No. 2015 / 152268 was placed in a nitrogen atmosphere, and dissolved in 161ml of dehydrated toluene. Then, 49.7ml of 20% methylaluminoxane / toluene solution manufactured by Albemarle was added at room temperature and stirred for 30 minutes. The 500ml three-neck flask containing the silica toluene slurry was heated and stirred in a 40°C oil bath, and the entire amount of the toluene solution of the reaction product of the zirconocene complex and methylaluminoxane was added. After stirring at 40° C. for 1 hour, the mixture was left to settle for 15 minutes while still heated at 40° C., and 224 ml of the supernatant was removed. The toluene solvent was then distilled off under reduced pressure to obtain a powder catalyst. (2) Production of ethylene-hexene copolymers; Using the powder catalyst obtained in (1) above, ethylene-hexene gas-phase continuous copolymerization was carried out. That is, polymerization was carried out while keeping the gas composition and temperature constant by intermittently feeding the powder catalyst at a rate of 0.62 g / hr into a gas-phase continuous polymerization apparatus (internal volume 100 L, fluidized bed diameter 10 cm, fluidized bed seed polymer (dispersant) 1.8 kg) prepared at a temperature of 75°C, a hexene / ethylene molar ratio of 0.46%, a hydrogen / ethylene molar ratio of 0.29%, a nitrogen concentration of 26 mol%, and a total pressure of 0.8 MPa. In addition, to keep the system clean, a hexane diluted solution of triethylaluminum (TEA) of 0.03 mol / L was fed to the gas circulation line at a rate of 15.7 ml / hr. As a result, the average production rate of polyethylene produced was 338 g / hr. The MFR and density of the ethylene-hexene copolymer obtained after producing 5 kg or more of polyethylene in total were 0.6 g / 10 min and 0.910 g / cm, respectively. 3 It was.

[0110] The density, MFR, molecular weight distribution Mw / Mn and Mz / Mw, and minimum branching index (g') in the molecular weight range of 100,000 to 1,000,000 of these components (B) C), and the proportion (X) of components eluted at 85°C or higher by temperature rising elution fractionation (TREF) are shown in Table 1.

[0111] [Table 1]

[0112] (3) Component (C) Nucleating Agent C1: Aluminum-di-para-tertiary butyl-hydroxybenzoic acid (manufactured by Dainippon Ink Co., Ltd., product name Al-PTBBA)

[0113] V. Working Examples <Example 1> A melt-kneaded mixture of 80 parts by weight of propylene homopolymer (MFR: 2.5 g / 10 min) as component (A) and 0.1 parts by weight of C1 aluminum-di-para-tert-butyl-hydroxybenzoic acid (manufactured by Dainippon Ink Co., Ltd., trade name Al-PTBBA) as component (C) was used, and an ethylene polymer LCB (MFR: 0.6 g / 10 min, density: 0.910 g / cm) was used as component (B). 3 A dry blend was obtained using 20 parts by weight of 1,2-dichlorophenyl ether (Mw / Mn=4.1).

[0114] This dry blend was molded into a sheet (III) according to the above-mentioned method, and the physical properties of the sheet (II) were evaluated. The results are shown in Table 2. The sheet exhibits extremely high low-temperature impact strength, is excellent in transparency and formability due to its melt tension, and also has high rigidity and impact strength at 23°C.

[0115] <Example 2> A dry blend was obtained in exactly the same manner as in Example 1, except that the blending ratios of component (A) and component (B) were changed from 80 parts by weight to 90 parts by weight and from 20 parts by weight to 10 parts by weight, respectively. The dry blend was molded into a sheet (III) according to the above-mentioned method, and the sheet properties (II) were evaluated, and the results are shown in Table 2. As shown in Table 2, the results are particularly excellent in stiffness, transparency, impact resistance, low-temperature impact strength, and moldability.

[0116] <Example 3> A dry blend was obtained in exactly the same manner as in Example 1, except that the blending ratios of component (A) and component (B) were changed from 80 parts by weight to 70 parts by weight and from 20 parts by weight to 30 parts by weight, respectively. The dry blend was molded into a sheet (III) according to the above-mentioned method, and the sheet properties (II) were evaluated, and the results are shown in Table 2. As shown in Table 2, the results showed that the rigidity was maintained at a good level, the transparency, impact resistance, and moldability were maintained at high levels, and the low-temperature impact strength was particularly excellent.

[0117] <Example 4> Component (A) was 80 parts by weight of propylene homopolymer (MFR: 2.5 g / 10 min), and component (B) was ethylene-based polymer LCB (MFR: 0.6 g / 10 min, density: 0.910 g / cm 3 A dry blend was obtained using 20 parts by weight of 1,2-dichlorophenyl ether (Mw / Mn=4.1).

[0118] This dry blend was molded into a sheet (III) according to the above-mentioned method, and the physical properties of the sheet (II) were evaluated. The results are shown in Table 2. The sheet exhibits extremely high low-temperature impact strength, excellent transparency, and moldability due to melt tension, as well as high rigidity and impact strength at 23°C.

[0119] <Comparative Example-1> In Example 1, only the melt-kneaded mixture of components (A) and (C) was used, and component (B) was not added. The obtained dry blend was molded into a sheet (III) according to the above-mentioned method, and the sheet properties (II) were evaluated, and the results are shown in Table 2. As shown in Table 2, the evaluation results showed that the transparency and rigidity were excellent, but the impact strength was low, and the moldability and low-temperature impact strength were poor.

[0120] <Comparative Example 2> In Example 1, component (B) was a high-pressure low-density polyethylene (LDPE: manufactured by Japan Polyethylene Co., Ltd., trade name Novatec LD LF122, MFR: 0.3 g / 10 min, density: 0.923 g / cm 3 ), a dry blend was obtained in exactly the same manner. The dry blend was molded into a sheet (III) according to the above-mentioned method, and the physical properties of the sheet (II) were evaluated, with the results shown in Table 2. As a result, as shown in Table 1, the molecular weight distribution Mw / Mn of component (B) measured by gel permeation chromatography (GPC) was outside the range of the present invention, and the minimum value (gc) of the branching index g' in the molecular weight range of 100,000 to 1,000,000 was below the lower limit of 0.40, so that the low-temperature impact strength was poor.

[0121] <Comparative Example-3> In Example 1, component (B) was a high-density polyethylene (HDPE: manufactured by Japan Polyethylene Corporation, trade name Novatec HD HB530, MFR: 0.3 g / 10 min, density: 0.964 g / cm 3 A dry blend was obtained in exactly the same manner, except that the density of component (B) was changed to 1.0, and the density of component (C) was changed to 1.0. The dry blend was molded into a sheet (III) according to the above-mentioned method, and the physical properties of the sheet (II) were evaluated, and the results are shown in Table 2. As shown in Table 2, the density of component (B) was outside the range of the present invention, and therefore the transparency was poor.

[0122] <Comparative Example-4> In Example 1, component (B) was a copolymer of ethylene and hexene (manufactured by Japan Polyethylene Co., Ltd., product name Kernel KS260, MFR: 2.2 g / 10 min, density: 0.902 g / cm 3 ), a dry blend was obtained in exactly the same manner. The dry blend was molded into a sheet (III) according to the above-mentioned method, and the physical properties of the sheet (II) were evaluated, with the results shown in Table 2. As shown in Table 2, the branching index g' of component (B) measured by a GPC measuring device combining a differential refractometer, a viscosity detector, and a light scattering detector had a minimum value (gc) of more than 0.85 for a molecular weight of 100,000 to 1,000,000, indicating poor moldability.

[0123] <Comparative Example-5> In Example 1, component (B) was a copolymer of ethylene and butene (manufactured by Japan Polyethylene Co., Ltd., trade name Novatec LL UF230, MFR: 1.1 g / 10 min, density: 0.921 g / cm 3 ), a dry blend was obtained in exactly the same manner. The dry blend was molded into a sheet (III) according to the above-mentioned method, and the physical properties of the sheet (II) were evaluated, and the results are shown in Table 2. As shown in Table 2, the catalyst used in producing component (B) was a Ziegler catalyst, so that the low-temperature impact strength was inferior to Examples 1 to 3 produced with a metallocene catalyst.

[0124] <Comparative Example-6> In Example 4, component (B) was a high-pressure low-density polyethylene (LDPE: manufactured by Japan Polyethylene Co., Ltd., trade name Novatec LD LF122, MFR: 0.3 g / 10 min, density: 0.923 g / cm 3 ), a dry blend was obtained in exactly the same manner. The dry blend was molded into a sheet (III) according to the above-mentioned method, and the physical properties of the sheet (II) were evaluated, with the results shown in Table 2. As a result, as shown in Table 1, the molecular weight distribution Mw / Mn of component (B) measured by gel permeation chromatography (GPC) was outside the range of the present invention, and the minimum value (gc) of the branching index g' in the molecular weight range of 100,000 to 1,000,000 was below the lower limit of 0.40, so that the low-temperature impact strength was poor.

[0125] [Table 2]

Claims

1. A method for producing a polyolefin resin composition containing at least 50 to 90% by weight of a polypropylene resin, component (A), and 10 to 50% by weight of a polyethylene resin, component (B), (wherein the total amount of components (A) and (B) is taken as 100% by weight), comprising: The method in which the polyethylene-based resin of component (B) is produced by a catalyst system which contains as an essential component a complex having a bridged (cyclopentadienyl)(indenyl) ligand and which uses silica as a fine particle support. (A) Polypropylene which may contain an α-olefin having 2 to 20 carbon atoms other than propylene as a comonomer, and has an MFR (JIS-K6758) of 0.1 to 50 g / 10 min. (B) A copolymer containing ethylene as a main component and an α-olefin having 3 to 18 carbon atoms, which satisfies the following conditions (B-1) to (B-5). (B-1) MFR (JIS-K7210) is 0.1 to 1.5 g / 10 min. (B-2) Density is 0.880 to 0.940 g / cm 3 . (B-3) The molecular weight distribution Mw / Mn measured by gel permeation chromatography (GPC) is 3.0 to 4.

5. (B-4) The molecular weight distribution Mz / Mw measured by GPC is 2.0 to 6.

0. (B-5) The minimum value (gc) of the branching index g' in the molecular weight range of 100,000 to 1,000,000, as measured by a GPC measuring device combining a differential refractometer, a viscosity detector and a light scattering detector, is 0.40 to 0.

85.

2. The method for producing a polyolefin resin composition according to claim 1, wherein the polyolefin resin composition further contains 0.03 to 2% by weight of a nucleating agent as component (C) (wherein the total amount of components (A) and (B) is taken as 100% by weight).

3. A method for producing a single-layer or multi-layer sheet having one or more layers made of a polyolefin resin composition, using a resin composition obtained by the method for producing a polyolefin resin composition according to claim 1 or 2.

4. A method for producing a molded article using a sheet obtained by the method for producing a sheet according to claim 3.

5. A method for producing a polyolefin-based resin composition comprising a polyethylene-based resin of component (B) below and a polypropylene-based resin of component (A) below, the resin composition being molded into a sheet and having a haze of less than 15% as measured according to JIS-K7105 "Testing methods for optical properties of plastics," comprising: The method in which the polyethylene-based resin of component (B) is produced by a catalyst system which contains as an essential component a complex having a bridged (cyclopentadienyl)(indenyl) ligand and which uses silica as a fine particle support. (A) Polypropylene which may contain an α-olefin having 2 to 20 carbon atoms other than propylene as a comonomer, and has an MFR (JIS-K6758) of 0.1 to 50 g / 10 min. (B) A copolymer containing ethylene as a main component and an α-olefin having 3 to 18 carbon atoms, which satisfies the following conditions (B-1) to (B-5). (B-1) MFR (JIS-K7210) is 0.1 to 1.5 g / 10 min. (B-2) Density is 0.880 to 0.940 g / cm 3 . (B-3) The molecular weight distribution Mw / Mn measured by gel permeation chromatography (GPC) is 3.0 to 4.

5. (B-4) The molecular weight distribution Mz / Mw measured by GPC is 2.0 to 6.

0. (B-5) The minimum value (gc) of the branching index g' in the molecular weight range of 100,000 to 1,000,000, as measured by a GPC measuring device combining a differential refractometer, a viscosity detector and a light scattering detector, is 0.40 to 0.

85.

6. A method for producing a sheet from a resin composition, comprising using the resin composition obtained by the method for producing a polyolefin-based resin composition according to claim 5 .

7. A method for producing a molded article using a sheet obtained by the method for producing a sheet according to claim 6.

Citation Information

Patent Citations

  • Polyolefin having long chain branch by ziegler-natta catalyst

    JP1985090203A

  • Polyethylene-based resin sheet

    JP1997031265A

  • Ethylene polymer

    JP1998298234A

  • Polyolefin resin composition, its sheet and its molded article

    JP2000072938A

  • Ethylene copolymer composition and use thereof

    JP2006312753A